Surgery at a glance - Grace, Pierce A; Borley, Neil R (Blackwell Science, 1999)
Concise guide and revision aid to undergraduate surgery. Each topic is presented as a double-page spread. Key facts are accompanied by line diagrams illustrating essential points. To be used to complement larger texts. For students. Softcover. DNLM: Surgical Procedures, Operative handbooks.
Keywords: chirurgie; General Surgery